Phase measurement errors due to holographic interferograms compression - Soraghan, John J. (2011)
Digital holographic interferometry allows accurate measurements on a microscopic level. As the number and size of the recorded digital holograms increase so does their data volume. As a result the volume of holographic data can substantially constrain applications where storage or transmittance of such data is required. Compression of holographic data in order to reduce their storage requirements has been studied. The speckled nature of the interferograms makes their compression nontrivial; however image compression algorithms such as JPEG, JPEG2000 and Set Partitioning In Hierarchical Trees (SPIHT) have been shown to perform adequately. So far the compression effects of the holographic interferograms using such coding methods have mainly been studied in terms of errors at the reconstruction intensity. On the other hand, metrology applications usually rely on the holograms’ reconstructed phase. In this paper we investigate hologram compression and how it affects the reconstructed phase. Holographic interferometry experiments are carried out to investigate measurement error due to interferograms compression using image compression methods. The results indicate that compression can be achieved while the measurement error due to compression is retained low.